'From Italian to Russian Soil Transplanted...’: “Vertogradets Sveta” and Its Italian Source - Космолинская, Галина (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2015)
The paper focuses on an unpublished manuscript known as Vertogradets Sveta, a translation from Italian carried out in the early 1730s by Pyotr Safonov. The translation was extremely popular throughout the 18th century. However, the name of the Italian author has not been known to the Russian readers. It is only now that the source of the text has been identified.